A Review of Plastic-derived Diesel Fuel as a Renewable Fuel for Internal Combustion Engines: Applications, Challenges, and Global Potential. Issue 1 (1st April 2022) - Nurdiyana Wan Mansor, Wan; Ashraf Razali, Nurul; Abdullah, Samsuri; Nor Khasbi Jarkoni, Mohammad; Busrya Eddy Sharin, Anis; Huda Abd Kadir, Nurul; Ramli, Aima; Chao, How-Ran; Lin, Sheng-Lun; Jalaludin, Juliana
Abstract: Plastics' broad application in a wide range of industries has resulted in an increase in global plastic production rates over time. The continued need for plastic, which can take up a lot of space in landfills due to the accumulation of plastic trash, has contributed to environmental problems. To address the problem of plastic waste, many options, such as recycling and energy recovery technologies, have been created. One possible technique to address landfill issues is to convert plastic waste into diesel fuel. In this review, the potential use of plastic-derived diesel fuel in internal combustion engines as a renewable and sustainable energy source is discussed. It's been found that due to similar properties in plastic-derived diesel fuel, it inherits similar performance in internal combustion engines.